Improving the safety and efficiency of emergency services emerging tools and technologies for first responders (Trending topics book series (TTBS) book series, 2020)
"This book addresses the latest tools that can support first responders in their ultimate goal: delivering their patients to safety. It also explores how new techniques and devices can support first responders in their work by addressing their safety, alerting them to accidents in real time, connecting them with medical experts to improve the chances of survival of critical patients, predicting criminal and terrorist activity, locating missing persons, and allocating resources"